Social Impact, Transparency and Compliance - Maria-Madalina COLTESCU; Mariana MAN (Social Sciences and Education Research Review, 2025)
This paper explores the level of compliance with integrated reporting regulations in Romania and the member states of the European Union, emphasizing the role of accountants in this process. Regulations impose non-financial reporting obligations, promoting transparency and social responsibility. In Romania, although integrated reporting is gaining traction, challenges persist regarding implementation and alignment with international standards (IIRC, GRI). The study highlights the essential contribution of accountants in ensuring corporate sustainability and compliance; however, significant differences exist among EU member states in terms of regulatory application. By outlining these differences and the challenges encountered, the research formulates recommendations for improving practices and aligning with European requirements. The limitations of integrated reporting include the lack of standardized data and legislative discrepancies. Future research directions focus on analyzing the impact of integrated reporting on financial performance and investor confidence. This study is relevant to both practitioners and policymakers, as it provides an updated perspective on the contribution of accountants to promoting transparency and corporate sustainability.